2016
DOI: 10.3727/096504016x14719078133528
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Open-Label Pilot Study of Simvastatin Addition to Whole-Brain Radiation Therapy in Patients With Brain Metastases

Abstract: Statins have been reported to have a potential radiosensitizing effect that has not been evaluated in clinical trials. The aim of this study was to evaluate the efficacy and safety of simvastatin in addition to whole-brain radiation therapy (WBRT) in patients with brain metastases (BM). A prospective randomized, controlled, open-label pilot study was conducted on 50 Egyptian patients with BM who were randomly assigned to receive 30-Gy WBRT (control group: 25 patients) or 30 Gy WBRT + simvastatin 80 mg/day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
(6 reference statements)
0
27
0
Order By: Relevance
“…Preclinical studies demonstrated that it induces apoptosis and inhibits tumor growth in a variety of cancer cells [12-14, 57, 58]. Combinations of simvastatin and an anticancer agent or radiotherapy have not been effective in patients with advanced cancer (Table 4) [59][60][61][62][63][64]; however, given simvastatin's wide-ranging physiological properties, there is still a need to evaluate the anticancer effect of simvastatin in combination with other types of anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies demonstrated that it induces apoptosis and inhibits tumor growth in a variety of cancer cells [12-14, 57, 58]. Combinations of simvastatin and an anticancer agent or radiotherapy have not been effective in patients with advanced cancer (Table 4) [59][60][61][62][63][64]; however, given simvastatin's wide-ranging physiological properties, there is still a need to evaluate the anticancer effect of simvastatin in combination with other types of anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Among 1008 articles identified from the literature search, 15 full-text articles were assessed for eligibility, of which eleven were ultimately eligible for inclusion ( Fig. 1) [21][22][23][24][25][26][27][28][29][30][31]. The four excluded articles met all inclusion criteria except for the outcomes of interest, instead focusing on surrogate outcomes [32][33][34][35].…”
Section: Search and Selection Of Studiesmentioning
confidence: 99%
“…Of the eleven RCTs, six originated from East Asia [23,[26][27][28][29]31]. Four studies were performed in Europe [21,22,24,30] and one in Egypt [25]. All studies were conducted in hospital-based settings.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations